An analysis of the nutrition status of neighboring Indigenous and non-Indigenous populations in Kanungu District, southwestern Uganda: Close proximity, distant health realities. (November 2018) - Sauer, Jeffery; Berrang-Ford, Lea; Patterson, Kaitlin; Donnelly, Blanaid; Lwasa, Shuaib; Namanya, Didas; Zavaleta, Carol; Ford, James; Harper, Sherilee
Abstract: Objectives: Malnutrition is a persistent health concern throughout the world. Globally, Indigenous peoples experience poorer health outcomes compared to their non-Indigenous neighbours. Despite this, malnutrition among Indigenous populations is poorly understood. This analysis estimated the prevalence, and modeled possible determinants of, moderate acute malnutrition (MAM) and severe acute malnutrition (SAM) for Indigenous Batwa and non-Indigenous Bakiga of Kanungu District in Southwestern Uganda. We then characterize possible mechanisms driving differences in malnutrition. Methods: Retrospective cross-sectional surveys were administered to 10 Batwa communities and 10 matched Bakiga Local Councils during April of 2014 ( n  = 1167). Individuals were classified as MAM and SAM based on middle upper-arm circumference (MUAC) for their age-sex strata. Mixed-effects regression models quantified the variation in malnutrition occurrence, considering individual, household, and community-ethnicity level effects. Models controlled for age, sex, number of dependents, education, and relative wealth. Results: Malnutrition is high among Batwa children and adults, with nearly half of Batwa adults (45.34%, 95% CI 34.82 to 55.86 for males; 45.86%, 95% CI 37.39 to 54.33 for females) and nearly a quarter of Batwa children (20.31%, 95% CI 13.07 to 26.93 for males; 25.81%, 95% CI 17.56 to 32.84 for females) meeting MAM criteria. SAM prevalence is lower than MAM prevalence, with SAM highest among adult Batwa males (11.60%, 95% CI 4.83 to 18.37) and adult Batwa females (3.00%, 95% CI 0.10 to 5.90). SAM prevalence among children was higher for Batwa males (7.03%, 95% CI 1.36 to 12.70) compared to Bakiga males (0.57%, 95% CI 0 to 1.69). Models that incorporated community ethnicity explained the greatest variance (>60%) in MUAC values. Conclusion: This research demonstrates a malnutrition inequality between the Indigenous Batwa and non-Indigenous Bakiga of Kanungu District, Uganda, with model results suggesting further investigation into the role of ethnicity as an upstream social determinant of health. Highlights: Malnutrition disparities exist among Indigenous and non-Indigenous groups in Uganda. Distinct malnutrition factors appear at individual, household, and community levels. Ethnic distinction within communities may act as an upstream determinant of health.